Awesome math : teaching mathematics with problem-based learning - Titu Andreescu; Kathy Cordeiro; Alina Andreescu (Hoboken, NJ : Jossey-Bass, 2020)
"Awesome Math builds on the popular growth mindset by focusing on team-based problem solving. Applying a problem-solving approach to the education process develops the skills necessary to think critically, creatively, and collaboratively. This book will help teachers and educators form lifelong communities for their students that will expose them to the collaborators they can network with in the future. Students need to move beyond the calculus trap and study the areas of mathematics most of them will need in the modern world and problem solving is an efficient vehicle to get them where they need to go. The book will cover: curiosity; critical thinking, and creativity; getting into the mathemize mindset; coaching mathletes and thinkers; math as a team sport; developing a community through problem solving; creating lesson plans; identifying and developing resources"-- Provided by publisher
Keywords: Instructional and educational works; Problem-based learning; Mathematics Study and teaching (Secondary)